ANALISIS PENGARUH STRUKTUR KEPEMILIKAN, BOARD SIZE, LEVERAGE, DAN GROWTH OPPORTUNITY TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris Pada Perusahaan BUMN Non Keuangan Yang Listing di Bursa Efek Indonesia Tahun 2010- 2013) - Dewi Novitasari, Clara; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2015)
One of the tecnique analyze to company performance used  profitability measured by ROA (Return On Asset). Return On Asset showed the effectiveness of company to get profit with asset . This research aimed to analyze the influence of state ownershipmanagerial ownership,, board size, leverage, and growth opportunity to profitability that measured by ROA. This research used control variable of  industry .            The number of sample in this research was 14 companies non-financial  listed on Indonesia Stock Exchange 2010-2013. The sampling method by using proposive sampling.  Analysis techniques used is Ordinary Least Square Regression (OLS), statistical t-test and classic assumption test that includes a test of normality test, multicollinearity test, heteroskedastisitas test, autocorrelation test.            The result showed that state ownership has negative significant association with  profitability.  The  managerial ownership  has  not significant with  profitability.  Board size has not significant with  profitability. Leverage has negative and  significant association  with  profitability , growth opportunity has positive and significant association profitability. Industries as control variable in this research hold the influence to state ownership, managerial ownership, board size, leverage, and growth opportunity with  profitability.